UNEMPLOYMENT AND YOUTH DISILLUSIONMENT: A SOCIAL WORK ANALYSIS OF JOBLESSNESS AND ITS SOCIAL IMPACT - Dr. Bharati Pramod Gaikwad (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Unemployment among youth is one of the most pressing socio-economic challenges confronting India today. With a rapidly growing population and limited employment opportunities, a significant segment of the country's educated youth finds itself without meaningful work. This condition not only leads to economic hardship but also contributes to a growing sense of disillusionment, frustration, and social alienation among the young population. This paper explores the multidimensional impact of youth unemployment through a social work lens, emphasizing its psychological, social, and economic consequences.